Análisis de las baterías de flujo como medio de almacenamiento de energía para el aplanamiento de pico de carga mejorando la eficiencia energética de la curva de demanda eléctrica. - Lema Osorio, Paúl Alfredo (2018)
This research work is focused on energy efficiency and sustainable development, which took into consideration one of the essential fields and currently developing energy storage, making a brief comparison between the different technologies and focusing on to conventional and flow batteries as a case study. A bibliographic compilation of data on the batteries was carried out to determine the advantages and disadvantages that they have in the economic, environmental, maintenance costs, implementation costs and the technical characteristics they have such as charge/discharge cycles, energy density, performance among other parameters. The researcher proceeded to use the historical data of the daily demand of an industry, later by analyzing this parameter, the rules of the tariff schedule of ARCONEL 007/00 were applied to evaluate its monthly consumption incidence and the benefits that have to correct the pattern of daily demand in its peaks and valleys to reduce the payment of the electric sheet using programs such as EXCEL for the simulation of load profiles, NEPLAN for flow diagrams and schemes. The mathematical financial formulas (NPV, IRR, NPV-INVERSION, and PAYBACK) were applied for the evaluation of the project, observing the economic viability for the implementation. The plan shows the economic benefits of leveling the load pattern according to the different time bands when applying the rate schedule. The application of the batteries in the Ecuadorian electrical system as an alternative for energy storage and leveling of the curve due to the low cost of electric power is not viable yet since in a predominance system of a hydraulic generation that is considered the cheapest compared to the other generation systems. Despite this observation, it is an excellent alternative for incorporation in non-conventional generation systems (solar, wind), due to its oscillation and storage difficulty. This research aimed to solve the necessity to select the appropriate technology when implementing the flow batteries (REDOX) in an industry, observing its technical and economic benefits, and the analysis to proceed to determine an implementation project of this technology and the curves resulting from the daily demand of the industry.